CALIFORNIA BEARING RATIO PADA TANAH LEMPUNG YANG DISTABILISASI DENGAN KALIUM HIDROKSIDA - Srie Gunarti, Anita Setyowati (BENTANG : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2013)
The minerals that make up soil that consists of elements and chemical compounds can react with other chemicals mixed in him. To the type of soil that inadequate technical ability but possessed with the chemical potential, can be enhanced by adding chemical substances which are chemical stabilization. The method used in this study is the method of chemical stabilization of the original soil by mixing with KOH powder chemicals and specific grafity test, standard proctor compaction and California Bearing Ratio Test Laboratory on original soil and the soil is mixed with the powder as much as 1% KOH and 2% are brooded for 24 hours. CBR test results showed a decrease of 7.6% CBR value of the original soil to soil mixed with powdered KOH 1%, and decreased by 22.5% CBR value of the original soil to soil mixed with 2% KOH powder. Key words: soil clay, KOH, CBR Laboratory, stabilization